Sales Information System Site Production for Mebel Era Jaya Sintang store - Willdo Benardi; Velwin Wibowo (JUDIMAS, 2021)
Era Jaya Furniture Store is a shop that sells various kinds of furniture in Sintang Regency. Problems that often arise in furniture stores usually occur in the bookkeeping and product data, which are often different in number because they are still using conventional bookkeeping, causing problems. From this problem arises the goal to solve the bookkeeping problem with the help of a Web-based sales system using a bootstrap framework. The form of research used in this research is a case study. The research method used is Design Science Research where in the process of identifying problems in solving problems, errors in bookkeeping are handled appropriately and effectively. Data collection techniques are non-participant observation, and in-depth interviews. Primary data obtained through observation and interviews, and secondary data obtained through journals. The bootstrap framework serves to make the website look more dynamic and make it easier for users to process data collection and transactions on the website, the advantages of using bootstrap on this website are the search system, tables, buttons, which are more dynamic and transitions on the website that make it easier for users to see what only features in the website. The result of this research is a sales website where the user is facilitated by using a dynamic and very responsive website display when used starting from the sidebar menu. The process of input, update, delete data is responsive because it is supported by the bootstrap framework.